2013
DOI: 10.3791/50038
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Function and Visualization of Cilia-Generated Fluid Flow in Kupffer's Vesicle

Abstract: Internal organs such as the heart, brain, and gut develop left-right (LR) asymmetries that are critical for their normal functions 1 . Motile cilia are involved in establishing LR asymmetry in vertebrate embryos, including mouse, frog, and zebrafish [2][3][4][5][6] . These 'LR cilia' generate asymmetric fluid flow that is necessary to trigger a conserved asymmetric Nodal (TGF-β superfamily) signaling cascade in the left lateral plate mesoderm, which is thought to provide LR patterning information for developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Unlike most embryonic cells, the DFCs retain cytoplasmic bridges with the yolk cell. Therefore, it is possible to deregulate gene expression specifically in these KV progenitors by targeting injections into the yolk syncytial layer (YSL) at the 1000-cell (1K) stage (Wang et al, 2013). At this point the YSL remains a syncytium that is non-contiguous with blastomeres of the embryo proper.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike most embryonic cells, the DFCs retain cytoplasmic bridges with the yolk cell. Therefore, it is possible to deregulate gene expression specifically in these KV progenitors by targeting injections into the yolk syncytial layer (YSL) at the 1000-cell (1K) stage (Wang et al, 2013). At this point the YSL remains a syncytium that is non-contiguous with blastomeres of the embryo proper.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the dynamics of flows inside the fish LRO (KV) has been more challenging due to its more sphere-like shape. Anticlockwise rotational flow patterns have been described in KV by tracking fluorescent microbeads using manual [34] or automated [35] approaches or by tracking laser-induced cellular debris [36]. Observations of flow dynamics indicated strong right-to-left flow in anterior region of the LRO and slower return right to left flow at posterior pole [31,37,38].…”
Section: Functions Of Cilia In Left -Right Patterning (A) Motile Cilimentioning
confidence: 99%
“…At the 256-cell stage, the bridge between yolk and DFCs/KV cells is open while other bridges between yolk and embryonic cells are closed, so that tMO can enter the progenitors of the DFCs through the cytoplasmic bridge without entering most other embryonic cells (Fig. 7A) (61). WISH analysis using the probe of sox17, which marks the DFCs and endoderm cells during the blastula stage, indicated that DFC migration and cohesion were not affected ( Fig.…”
Section: Identification Of Sept6 In Zebrafishmentioning
confidence: 99%
“…KV is a ciliated, fluid-filled organ in zebrafish that plays a critical role in nodal signaling and LR development (38,60,61). Because septins are known to localize at the base of primary cilia and affect cilium-based signaling in other vertebrate cells (13,25), we reasoned that sept6 may affect LR asymmetry in zebrafish by regulating ciliogenesis in KV.…”
Section: Identification Of Sept6 In Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation